Institusionalisasi akad muamalah - Ali Amin Isfandiar (Jurnal Investasi Islam, 2020)
Islamic contract mechanism, as it's called al-'aqd al-muamalah) was doneas personal contract. The emerging of islamic bank makes it transfrormed being aninstitution contract, that changes a simple contract being a rigid one, because aposition of the islamic bank. This process is called by "institutionalization", where itcould be realized without external power which support that process, such as policypower who arranges by rules, internal resources who prepars software, hardware andbrainware, economi power who supports market acceptance analysis, social powerwho supports accelerated improvement and inovation, and ijtihad power who supportssyariah compliance. The three latest are research focus and by social economicapproach and qualitative analysis model, this research finds that theinstitutionalization of islamic contract has been transforming for a long-long time agoand using two ways scientifically integration process, economics and syariah (islamiclaw), especially al-fiqh al-mu'ámalah.